Micron- and nano-cellulose fiber regenerated from ionic liquids. Issue 4 (2nd April 2016) - Vinogradova, Yevgeniya S.; Chen, Jonathan Y.
Abstract : In this research, two types of ionic liquid, 1-butyl-3-methylimidazolium chloride (BMIMCl) and ionic liquid 1-ethyl-3-methylimidazolium acetate (EMIMAc), were used as recyclable solvents for dissolving raw cellulose in the spinning of micron- and nano-scale regenerated cellulose fiber. The approach for preparing the cellulose solution using these ionic liquids is described. A comparative study was also conducted on cellulose solubility, the spinning method, and cellulose fiber properties produced with each solvent. The experimental fibers are characterized in terms of fiber diameter, strength, thermal property, crystallinity, and content of solvent residual, using tensile test, thermogravimetric analysis, scanning electron microscopy, X-ray diffraction, and mass spectrometry. The study concluded that there was a significant difference in the tensile strength, but not in the elongation and modulus of the fibers regenerated from BMIMCl and EMIMAc. For crystal size, crystal orientation, and crystallinaty index, the BMIMCl-generated fiber had higher values than the EMIMAc-regenerated fiber. For the thermal property, EMIMAc fiber was more stable at higher temperatures than BMIMCl fiber. It was also revealed that the EMIMAc fiber had significantly less solvent residual content than the BMIMCl fiber.